The feeding preferences of Spodoptera frugiperda (J. E. SMITH) (Lepidoptera: Noctuidae) on cotton plant varieties=Preferência alimentar de Spodoptera frugiperda (J. E. SMITH) (Lepidoptera: Noctuidae) em variedades de plantas algodoeiras - Ostenildo Ribeiro Campos; Walter Veriano Valério Filho; Arlindo Leal Boiça-Júnior; Zeneide Ribeiro Campos; Alcebíades Ribeiro Campos (Acta Scientiarum: Agronomy, 2012)
This work evaluated the attractiveness and the non-preference for feeding of newly hatched fall armyworm larvae on the cotton plant parts and different varieties used in the study. The trials were performed at 27 ± 1ºC, a 70% ± 10% relative humidity and a 14h photoperiod. Leaves, bracts, squares and carpel walls of the BRS Itamarati-90 variety and leaves of Fibermax-966, Fibermax-977, DeltaOpal, DeltaPenta, BRS Acala-90, Coodetec-408, Coodetec-409, Coodetec-410, BRS-Cedro, BRS-Ipê, BRS-Aroeira, IPR-96, IPR-120, BRS-Araçá, IAC-24 and BRS Itamarati-90 varieties were used in attractiveness, multiple-choice and confinement (no-choice) non-preference feeding trials. Twenty larvae were released per petri dish test (arena system) with 10 repetitions. Attractiveness trials were evaluated by counting feeding caterpillars over 60 min. and by measuring non-preference at 24h. Leaves were the most attractive item and were preferred for feeding. In the multiple-choice arena trials, Coodetec-410 was the most attractive variety, and BRS Acala-90, Fibermax-966 and DeltaPenta were the least attractive to fall armyworm larvae. In the non-preference trial, BRS-Araça was the variety favored for feeding. BRS-Cedro, BRS Itamarati-90, DeltaPenta, Coodetec-408 and BRS-Aroeira were the least-favored varieties. In the 60 min. attractiveness trials, 46 min. proved to be the most suitable time for evaluating the attractiveness of cotton plants to newly hatched fall armyworm larvae. Avaliou-se atratividade e não-preferência alimentar de lagartas recém-eclodidas de Spodoptera frugiperda por partes de plantas e plantas de variedades de algodoeiro. Testes foram realizados a 27 ± 1ºC, UR de 70% ± 10% e fotofase de 14h. Folhas, brácteas, botões florais e cascas de maçãs da variedade BRS Itamarati-90 e folhas de Fibermax-966, Fibermax-977, DeltaOpal, DeltaPenta, BRS Acala-90, Coodetec-408, Coodetec-409, Coodetec-410, BRS-Cedro, BRS-Ipê, BRS-Aroeira, IPR-96, IPR-120, BRS-Araçá, IAC-24 e BRS Itamarati-90 foram utilizadas nos testes de atratividade e não-preferência para alimentação, com e sem chance de escolha. Utilizaram-se 20 lagartas de S. frugiperda por placa de Petri (sistema de arena) por teste, com 10 repetições. Contaram-se lagartas para avaliar atratividade por 60 min e não-preferência para alimentação por 24 h. Folha foi mais atrativa e preferida para alimentação por lagartas de S. frugiperda. Em livre escolha, Coodetec-410 foi mais atrativa e BRS Acala-90, Fibermax-966 e DeltaPenta, as de menor atratividade à S. frugiperda; BRS-Araçá, mais preferida para alimentação e BRS-Cedro, BRS Itamarati 90, DeltaPenta, Coodetec-408 e BRS-Aroeira, menos preferidas. Considera-se 46 min., tempo mais adequado para avaliar atratividade de algodoeiro a lagartas de S. frugiperda.